x+(91-2x)=247

Simple and best practice solution for x+(91-2x)=247 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x+(91-2x)=247 equation:


Simplifying
x + (91 + -2x) = 247

Remove parenthesis around (91 + -2x)
x + 91 + -2x = 247

Reorder the terms:
91 + x + -2x = 247

Combine like terms: x + -2x = -1x
91 + -1x = 247

Solving
91 + -1x = 247

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-91' to each side of the equation.
91 + -91 + -1x = 247 + -91

Combine like terms: 91 + -91 = 0
0 + -1x = 247 + -91
-1x = 247 + -91

Combine like terms: 247 + -91 = 156
-1x = 156

Divide each side by '-1'.
x = -156

Simplifying
x = -156

See similar equations:

| (9x³+3x²-15x)/(-3x) | | (x-45)=89 | | 0.33(x-1)=29 | | 5x-2(x+3)=90 | | 6x=22 | | Y=2x-3 | | Y=-x-1 | | Y=0.3x-8 | | Y=0.3-8 | | -40=m-10m | | 8t-5t=-25 | | -7u=20 | | 4r=17 | | 8.8+4X=40 | | -8x=56 | | 4X-18+4=8 | | 5X+X-1.1=5.5 | | 16x+4(2x-6)=60 | | 3.6=5.4+3.3y | | 8+16n-4=5n+108-2n | | -4x-9x= | | 27+7u+8u-17=20u+17-5u-7 | | -5n+9=-4n-5 | | -8c+7=-1 | | -3=4x+6-x | | 7x+3+6x+9=12x+5 | | -9c+1=-17 | | -9c+1=17 | | 6z-6-10z=39+10z+4 | | x+3=25 | | 6z-6-10z=39 | | 5(5c-1)-5=23c+6 |

Equations solver categories